2012
DOI: 10.1111/j.1600-0722.2012.00948.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental risk factors for submucous cleft palate

Abstract: A multifactorial aetiology with genetic and environmental factors is assumed for orofacial clefts. Submucous cleft palate (SMCP), a subgroup of cleft palates with insufficient median fusion of the muscles of the soft palate hidden under the mucosa, has a prevalence of 1:1,250-1:5,000. We described the prevalence of risk factors among 103 German patients with the subtype SMCP and genotyped 24 single nucleotide polymorphisms (SNPs) from 12 candidate genes for orofacial clefts. Analysis of risk factors yielded a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 48 publications
1
32
2
Order By: Relevance
“…Combining our results with those provided in the literature, 9,[11][12][13][14] eight patients are recorded with palatal defects in association with a 22q12 deletion, involving the MN1 gene. These observations, together with an increased MN1 SNP frequency in patients with submucous cleft palate, 20 with the mouse expression data and the finding of craniofacial malformations including cleft palate in a Mn1-knockout mouse model further suggest that this gene contributes to the cleft palate observed in the reported patients.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Combining our results with those provided in the literature, 9,[11][12][13][14] eight patients are recorded with palatal defects in association with a 22q12 deletion, involving the MN1 gene. These observations, together with an increased MN1 SNP frequency in patients with submucous cleft palate, 20 with the mouse expression data and the finding of craniofacial malformations including cleft palate in a Mn1-knockout mouse model further suggest that this gene contributes to the cleft palate observed in the reported patients.…”
Section: Resultssupporting
confidence: 71%
“…20 Moreover, Mn1 acts as a transcriptional activator of Tbx22 during palatal development in mice. 21 Variants in the human TBX22 gene have been associated with X-linked cleft palate and ankyloglossia 22,23 and with isolated CP.…”
Section: Discussionmentioning
confidence: 99%
“…Submucous cleft palate is a subgroup of cleft palates with insufficient median fusion beneath the mucosal layer. 3 A submucous cleft of the soft palate is characterized by a midline deficiency in muscular tissue and subsequent incorrect positioning of the muscles, whereas a submucous cleft of the hard palate is defined as a bony defect in the midline of the hard palate. 4 Often, a submucous cleft palate is associated with a bifid or cleft uvula.…”
Section: Figurementioning
confidence: 99%
“…In contrast to CL/P, the genetic architecture of CPO and SMCP is poorly understood. Although previous candidate gene-based association studies have identified SMCP candidate loci [Reiter et al, 2012], no genome wide association study (GWAS) in SMCP has been performed to date. Conversely, several GWAS and meta-analyses have identified common variants associated with CL/P [Birnbaum et al, 2009;Beaty et al, 2010;Mangold et al, 2010;Ludwig et al, 2012], including a key susceptibility SNP on chromosome 8 (rs987525) that is consistently associated with CL/P across different populations but shows no association with CPO [Birnbaum et al, 2009;Grant et al, 2009;Ludwig et al, 2012;Uslu et al, 2014].…”
Section: To the Editormentioning
confidence: 99%
“…While a single GWAS in CPO has tentatively implicated gene x environment interactions , no locus with genome wide significant association has been reported in CPO to date. Similarly, there may be genetic and environmental factors jointly influencing the risk of SMCP, such as gene x smoking interactions [Reiter et al, 2012]. The lower incidence of CPO and SMCP and their presumed higher genetic heterogeneity when compared to CL/P might be reasons for the paucity of CPO and SMCP risk alleles reported to date.…”
Section: To the Editormentioning
confidence: 99%